Critical Study of Fatigue Behaviour of a Cement Matrix Composite Reinforced by Sugar Cane Bagasse Short Fibers - Pamphile, Acodji V.; Valery, Doko K.; Emmanuel, Olodo E. T. (New Ideas Concerning Science and Technology Vol. 6, 2021)
This work is devoted to the study of the fatigue behaviour of a cement matrix composite reinforced by sugar cane bagasse short fibers. The understanding of its fatigue behaviour is interesting for the dimensioning of parts using it for material. The objective is analysis of the fatigue behaviour in order to assess its ability to withstand use on wall structures, in bracing, false ceiling of this material. Some series of tests carried out in compression and flexion characterized the material mechanical properties, the tests in monotonic and cyclic three-point bending showed the material behaviour in use. For the composite, another fairly conventionally used representation is to visualize the variations in material properties as a function of the number of cycles. The Wöhler curves is plotted from the strain stresses and the number of cycles for the end of test criteria. It shows the influence of increase in stress on the material service life face of breaking. The Fatigue limit corresponds to the line s =26.40 MPa, stress for which no breaking is observed after an infinite number of cycles, and the Endurance limit corresponds to the line of stress 26.79 MPa, the limit value towards which the stress amplitude tends when the number of cycles becomes very large. This information allows us to control the quality of the material by building a tolerance interval below which the pieces are deemed non-compliant.